Confecção de argamassa com a substituição total do agregado natural por agregados provenientes de resíduo de construção e demolição (RCD) - SOUZA, Grazielle Tigre de (2022)
The industry of civil construction stands out as a productive sector, which has a significant role in the national economy. However, this sector stands out as an activity that generates a high amount of waste of various kinds, and also responsible for excessive consumption of natural resources, from non-renewable sources. The recycling of waste from this production chain performs an important role for sustainability, promoting conservation of natural resources and the reduction of areas for final disposal. The primary focus of this research is the study of utilization the Waste of Construction and Demolition (WCD), contributing to the development of alternative materials. In this sense, the main objective of this research is evaluate the use of RCD generated in Tucuruí Hydropower Plant, as fine aggregate in the production of mortars, considering replacing 100% of the natural aggregate. Were conducted laboratory tests designed to evaluate the RCD characteristics and subsequently produced mortars with trace of 1: 5 and evaluated the proprieties in its fresh and hardened condition, comparing them with the behavior of the reference mortar with natural sand. The results obtained in the experimental procedure presented technological potential for use in replacement of natural aggregate, representing one alternative that contribute to sustainability in construction.